F75 A huntington's disease (HD) database at lirh foundation (LIRH-rome site): enroll-hd study as a starting point. (September 2018) - Dema, Maria Giovanna; Borrelli, Cristiana; Migliore, Simone; Fusilli, Caterina; Maffi, Sabrina; Santimone, Iolanda; Gabriele, Maria; Belcastro, Loris; D'Alessio, Barbara; Squitieri, Ferdinando
Abstract : Background: LIRH Foundation started to collect data from HD subjects and families since 2001. The collection includes data from LIRH archives, REGISTRY (since 2004) and ENROLL-HD (since 2014) data. Aims: To develop a large HD database starting from ENROLL-HD data. Methods: The database was constructed through shiny, plyr and DT R packages (R 3.4.4 version) for automatically merging different clinical items. Results: Since July 2014, we recruited 626 people into ENROLL-HD, until May 2018. Follow-ups are available for 432 subjects (one-year), 268 (two-years) and 152 (three years). Our cohort includes 404 gene positive (346 patients and 58 pre-manifest) individuals, 153 genetically 'unknown' (50% at risk), 36 gene negative and 43 family member subjects. Mean age at onset is 47, 6±14, 7 (range 7–86), thus including adolescent (<20 years, N=15 subjects), children (<10 years; N=5 subjects) and late onset (>60 years; N=35 subjects) cohorts. Onset symptoms includes motors signs in 47, 9%, mixed in 34, 9%, psychiatric in 15.6% and cognitive in 1.5% cases. Suicide ideation occurred in 17, 4%, calculated according to the C-SSRS scale activation. Mean, fully penetrant expanded repeat number is 44, 4±5, 06 (range 40–84); two 2 subjects have intermediate alleles (29, 5±0, 7; range 29–30), and 23 reduced penetrance (38, 2±0, 8; range 36–39). Disease stage, according to the TFC scale score (9, 7±3, 9; range 1–13), ranges between 1 to 5. Conclusions: A proper database and stratification of HD subjects according to genetic condition, symptom presentation, mutation length and development of further symptoms is crucial for both improving the disease knowledge and to driving people to research plans.